Vertical nanowire electrode arrays as a scalable platform for intracellular interfacing to neuronal circuits - Robinson, Jacob T. (2012)
Deciphering the neuronal code - the rules by which neuronal circuits store and process information - is a major scientific challenge(1,2). Currently, these efforts are impeded by a lack of experimental tools that are sensitive enough to quantify the strength of individual synaptic connections and also scalable enough to simultaneously measure and control a large number of mammalian neurons with single-cell resolution(3,4). Here, we report a scalable intracellular electrode platform based on vertical nanowires that affords parallel electrical interfacing to multiple mammalian neurons. Specifically, we show that our vertical nanowire electrode arrays (VNEAs) can intracellularly record and stimulate neuronal activity in dissociated cultures of rat cortical neurons and can also be used to map multiple individual synaptic connections. The scalability of this platform, combined with its compatibility with silicon nanofabrication techniques, provides a clear path toward simultaneous, high-fidelity interfacing with hundreds of individual neurons.